Application of a novel anvil holder clamp in laparoscopic gastrectomy - Qi, Yuhai; Li, Linchuan; Li, Bo; Hu, Sanyuan; Zhu, Jiankang; Zhang, Guangyong (Frontiers in Oncology, 2025)
BackgroundThe reverse puncture method is a common reconstruction technique used in radical gastrectomy for gastric cancer. However, its widespread use is limited due to unstable clamping and unstable force directions, which complicate the anastomosis process. Therefore, we aimed to develop an improved clamp and investigated its application during the anastomotic process.MethodsThis retrospective study included 29 patients who underwent laparoscopic-assisted Roux-en-Y total gastrectomy (n=16) or laparoscopic-assisted gastric tube proximal gastrectomy (n=13), utilizing reverse puncture circular anastomosis techniques during surgery. Intraoperatively, the anterior wall of the esophagus was opened using an anvil holder clamp to position the anvil, and a circular stapler was used to transect the esophagus. Finally, circular anastomosis was completed with assistance from our anvil holder clamp. We assessed the number of clamping attempts, time at each stage, clinical characteristics, and surgical outcomes.ResultsAll patients underwent successful laparoscopic radical gastrectomy. The mean number of attempts in the two stages was 1.14 and 1.03. The mean duration for these two procedures was 22.6 s and 27.9 s. The overall incidence of postoperative complications (Clavien–Dindo classification grade ≥II) was 17.2%. Esophagojejunostomy leakage occurred in one case (3.4%). Patients with anastomotic leakage were successfully managed with conservative treatment, with no cases of mortality.ConclusionOur improved clamp is simple, safe, and effective for the anastomotic laparoscopic gastrectomy procedure and may benefit its wide application.